The 'New Firm Paradigm' and the Provision of Training: The Impact of ICT, Workplace Organization and Human Capital - Heinz Hollenstein; Tobias Stucki (Swiss Journal of Economics and Statistics, 2012)
The paper analyzes the relevance of the three constituent elements of the `new firm paradigm', i.e. ICT, workplace organization and human capital, as determinants of a firm's provision of training. We concentrate on apprenticeship training, which in German-speaking countries is a widespread practice of skill formation. Econometric studies dealing with a firm's provision of apprenticeships so far did not pay much attention to the inf luence of a shift towards the new paradigm. We find that apprenticeship training is an appropriate way of skill formation in advanced economies, but this may not be the case in leading-edge segments of the economy.
Keywords: J2; L2; O3; M5; 330; Firm-based training; apprenticeship; ICT; workplace organization; human capital formation